2021
DOI: 10.1007/s10708-021-10486-3
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven remote governance of sparsely populated areas: measurement and commensuration of wildcat gold mining in French Guiana

Abstract: The increase in the price of gold, due to a shift to safe investments during the global economic crisis, has led to a rapid expansion of gold production. Alongside legal gold mines, wildcat gold mining has developed in French Guiana since the early 2000s. This phenomenon, with its social, environmental and economic consequences, is at the heart of the environmental governance of this territory. However, its difficult quantification is the subject of multiple controversies. Environmental governance is increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The main challenge of creating a scenario is data availability. Data availability and uncertainty represent basic but fundamental issues, especially in data-limited environments and sparsely populated areas [31,95,96], and when the assessment process switches across multiple spatial scales, implying the need of spatial precision requirements [97]. This is the case in FG, where the difficulty of access on the whole territory limits available data or drives extrapolation processes that provide coarse data at the territory level.…”
Section: Data Availability: a Specific Focus On Illegal Gold Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…The main challenge of creating a scenario is data availability. Data availability and uncertainty represent basic but fundamental issues, especially in data-limited environments and sparsely populated areas [31,95,96], and when the assessment process switches across multiple spatial scales, implying the need of spatial precision requirements [97]. This is the case in FG, where the difficulty of access on the whole territory limits available data or drives extrapolation processes that provide coarse data at the territory level.…”
Section: Data Availability: a Specific Focus On Illegal Gold Miningmentioning
confidence: 99%
“…Concerning gold mining, particular attention should be given to illegal and informal gold mining, which is regarded as a worldwide challenge [98] for mining and socioenvironmental regulatory frameworks [99]. Focusing on the analysis of illegal gold mining related data, the authors of [96] suggested that the central problem in FG is the information marginalization and the qualification of the data, which is never raw and is accentuated by the difficulties in accessing to the field.…”
Section: Data Availability: a Specific Focus On Illegal Gold Miningmentioning
confidence: 99%